Contribution of TRNA modifications for proteostasis in human cells - Paulo, Cristiana Gonçalves (2020)
Mutations in transfer RNAs (tRNA), key molecules in the translation process, lead to loss of accuracy of messenger RNA (mRNA) translation. This may induce changes in protein synthesis rate, protein misfolding and accumulation of aggregated proteins which, in turn, leads to proteotoxic stress and UPR activation, some of the characteristics of conformational protein diseases. To be fully active, tRNA molecules undergo post-transcriptional modifications catalyzed by different tRNA modifying enzymes. Deregulation of some modifications of tRNAs and some of the modifying enzymes has already been correlated with changes in translation fidelity and efficiency, especially in yeast. However, a comprehensive study on the impact of all tRNA-modifying enzymes and modifications in mammals has not been performed yet. In order to identify the key modifying enzymes for proteostasis preservation, our team developed a protein aggregation reporter system (pcDNA3.1 Hsp27-GFP) that allows the detection of the production of protein aggregates in vivo at the cellular level. After establishing a stable cell line expressing this reporter, a phenotypic screening was performed, identifying ELP1, ELP3, ELP6, URM1 and TRMT2A enzymes as essential for proteostasis. The UPS pathway was activated in the absence of the ELP1, ELP3, ELP6 enzymes and proteomic analyzes of ELP3 silencing cells revealed that the most altered pathways are concerned to transcription and translation processes, which are generally dysregulated in neurological diseases, such as Amyotrophic Lateral Sclerosis. In this thesis, the proteostasis relevant tRNA modifying enzymes are identified and characterized in human cells. This group of enzymes may represent promising therapeutic targets for conformational diseases